A systematic review of tools used to screen and assess for externalising behaviour symptoms in low and middle income settings. (2019) - Nezafat Maldonado, B.; Chandna, J.; Gladstone, M.
Abstract : Background: Mental health issues, often manifested as behavioural difficulties, in children are estimated to be high in low and middle-income countries (LMIC) settings. There is a paucity of definitive data due to a lack of well-validated tools to use across settings. This review aims to provide evidence on what tools are used and which have been adapted and validated in LMIC settings. Methods: We performed a systematic review to identify tools used to assess or screen externalising behaviour problems in children and adolescents in LMIC and assess their cultural adaptations. We searched for studies measuring externalising behaviour in children from 0 to 19 years published up to September 2018. Articles were assessed to identify tools used and analysed using the Ecological Validity Framework. Results: We identified 82 articles from over 50 LMICs who had studied externalising behaviour in children. Twenty-seven tools were identified, with a predominance of studies using tools from the USA and Europe. Most studies did not describe an adaptation and evaluation process, with only one study following recommended criteria. New tools were identified which both screen and assess externalising behaviour which have not yet been utilised across settings. Conclusions: Although tools from the USA and Europe are often utilised to screen and assess for externalising behaviour problems in children in LMICs, the conceptual frameworks behind the use of these tools in other cultural contexts are not always carefully examined. In order to have valid data across cultures, we should aim to adapt and validate tools before use. Provision of processes to validate tools across LMIC settings would be beneficial.